A generalised approach to the use of sampling for rapid object location - Davies, Roy (Zielona Góra: Uniwersytet Zielonogórski)
This paper has developed a generalised sampling strategy for the rapid location of objects in digital images. In this strategy a priori information on the possible locations of objects is used to guide the sampling process, and earlier body-based and edge-based approaches emerge automatically on applying the right a priori probability maps. In addition, the limitations of the earlier regular sampling technique have been clarified and eased - with the result that sampling patterns are better matched to the positions of the image boundaries.
Keywords: machine vision; automated inspection and assembly; rapid object location; sampling techniques